Examining U.S. approvals of Islamic financing products and the Islamic theory of lawful profit - Abdullah, Adam (Emerald Group Publishing, 2016)
Purpose: This paper seeks to analyze the legal interpretation of three Islamic financing products considered for approval by United States authorities, from the United Bank of Kuwait and Guidance Residential, even though the U.S. has not enacted any Shari’ah legislation in relation to the Islamic law of transactions (fiqh mu’amalat). Design/methodology/approach: This paper primarily adopted qualitative document and content analysis, supported by quantitative numerical analysis, in reviewing legal interpretive letters from the U.S. Office of the Comptroller of Currency and National Administrator of Banks (OCC) and the U.S. Department of Revenue. Findings: The research found that in assessing economic substance over legal form, each of the three products involved risk-free transactions and interest. Research limitations/implications: The research had access to published OCC, Department of Revenue and U.S. Patent Office material that fully disclosed the mechanics of each of the selected products. Practical implications: The implication for the Islamic financial institutions involves Shari’ah compliance risk. When tested against the Islamic normative theory of lawful profit, it confirms that the products are non-compliant. Social implications: The social implication is customer awareness of Shari’ah non-compliance in the U.S., and the impact for other jurisdictions carrying the same products. Originality/value: The significance of this research for Islamic banking product design and development, is that it enhances the ability to block the legal means to an unlawful outcome (sadd al-dhara’i), thereby avoiding harm (al-darar) attributed to usury (riba), and upholding what is in the public interest (maslahah), in order to fulfil one of the objectives of the Shari’ah (maqasid al-Shari’ah), which is to protect wealth (hafiz al-mal).